Diversity and drivers of marine heatwaves in the Beibu Gulf of the South China Sea - Bo Zhang; Qiang Wang; Lili Zeng; Kunshan Li; Yi Xie; Rui Shi (Climate Dynamics, 2026)

Estimation of daily net radiation based on the continuous meteorological data observed from different underlying surfaces - Rongxuan Bao; Haofang Yan; Chuan Zhang; Guoqing Wang; Jianyun Zhang; Desheng Zhang; Yudong Zhou; Biyu Wang; Xuanxuan Wang; Rui Zhou; Youwei Liu; Yujing Han (Climate Dynamics, 2026)

Synergic influence of lower and upper troposphere large-scale circulations on tropical cyclone genesis over the western North Pacific - Yiran Wang; Chao Wang; Liguang Wu; Rui Zhao; Haikun Zhao; Jian Cao (Climate Dynamics, 2024)

Influence of the Southern Ocean Dipole on the inter-model diversity of temporal trend of the austral summer Southern Annular Mode in CMIP6 models - Rui Wang; Fei Zheng; Xiaofeng Li (Climate Dynamics, 2024)

Evaluation of the performance of the latest WRF model (V4.5) in simulating surface elements and its sensitivity to the diurnal SST cycle in the South China Sea - Rui Shi; Ju Chen; Yunkai He; Wei Song; Daning Li; Yeqiang Shu; Dongxiao Wang (Climate Dynamics, 2024)

Correction to: Uncertain role of clouds in shaping summertime atmosphere‑sea ice connections in reanalyses and CMIP6 models - Rui Luo; Qinghua Ding; Ian Baxter; Xianyao Chen; Zhiwei Wu; Mitchell Bushuk; Hailong Wang (Climate Dynamics, 2023)

Uncertain role of clouds in shaping summertime atmosphere-sea ice connections in reanalyses and CMIP6 models - Rui Luo; Qinghua Ding; Ian Baxter; Xianyao Chen; Zhiwei Wu; Mitchell Bushuk; Hailong Wang (Climate Dynamics, 2023)
Downwelling longwave radiation (DLR) driven by the atmospheric and cloud conditions in the troposphere is suggested to be a dominant factor to determine the summertime net surface energy budget over the Arctic Ocean and thus plays a key role to shape the September sea ice. We use reanalyses and the self-organizing map (SOM) method to distinguish CMIP6 model performance in replicating the observed strong atmosphere-DLR connection. We find all models can reasonably simulate the linkage between key atmosphere variables and the clear sky DLR but behave differently in replicating the atmosphere-DLR connection due to cloud forcing. In ERA5 and strongly coupled models, tropospheric high pressure is associated with decreased clouds in the mid- and high-levels and increased clouds near the surface. This out-of-phase structure indicates that DLR cloud forcing is nearly neutral, making the clear sky DLR more important to bridge JJA circulation to late-summer sea ice. In MERRA-2 and weakly coupled models, tropospheric clouds display a vertically homogeneous reduction; the cloud DLR is thus strongly reduced due to the cooling effect, which partially cancels out the clear sky DLR and makes the total DLR less efficient to translate circulation forcing to sea ice. The differences of cloud vertical distribution in CMIP6 appear to be differentiated by circulation related relative humidity. Therefore, a better understanding of the discrepancy of different reanalyses and remote sensing products is critical to comprehensively evaluate simulated interactions among circulation, clouds, sea ice and energy budget at the surface in summer.

Impact of Arctic amplification on declining spring dust events in East Asia - Jun Liu; Dongyou Wu; Guangjing Liu; Rui Mao; Siyu Chen; Mingxia Ji; Pingqing Fu; Yele Sun; Xiaole Pan; Hongchun Jin; Yubin Zhou; Xin Wang (Climate Dynamics, 2020)
Dust aerosols play key roles in affecting regional and global climate through their direct, indirect, and semi-direct effects. Dust events have decreased rapidly since the 1980s in East Asia, particularly over northern China, primarily because of changes in meteorological parameters (e.g. surface wind speed and precipitation). In this study, we found that winter (December–January–February) Arctic amplification associated with weakened temperature gradients along with decreased zonal winds is primarily responsible for the large decline in following spring (March–April–May) dust event occurrences over northern China since the mid-1980s. A dust index was developed for northern China by combining the daily frequency of three types of dust event (dust storm, blowing dust, and floating dust). Using the empirical orthogonal function (EOF) analysis, the first pattern of dust events was obtained for spring dust index anomalies, which accounts for 56.2% of the variability during 1961–2014. Moreover, the enhanced Arctic amplification and stronger Northern Hemisphere annular mode (NAM) in winter can result in the anticyclonic anomalies over Siberia and Mongolia, while cyclonic anomalies over East Europe in spring. These results are significantly correlated with the weakened temperature gradients, increased precipitation and soil moisture, and decreased snow cover extent in the mid-latitude over Northern Hemisphere. Based on the future predictions obtained from the Fifth Climate Models Intercomparison Project (CMIP5), we found that the dust event occurrences may continually decrease over northern China due to the enhanced Arctic amplification in future climate.

The roles of tropical and subtropical wind stress anomalies in the El Niño Modoki onset - Xin Wang; Chengyang Guan; Rui Xin Huang; Wei Tan; Lei Wang (Climate Dynamics, 2019)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

On the development of a coupled regional climate–vegetation model RCM–CLM–CN–DV and its validation in Tropical Africa - Guiling Wang; Miao Yu; Jeremy S. Pal; Rui Mei; Gordon B. Bonan; Samuel Levis; Peter E. Thornton (Climate Dynamics, 2016)

Decadal changes in tropical cyclone activity over the western North Pacific in the late 1990s - Haozhe He; Jing Yang; Daoyi Gong; Rui Mao; Yuqing Wang; Miaoni Gao (Climate Dynamics, 2015)

Rain follows logging in the Amazon? Results from CAM3–CLM3 - Rui Mei; Guiling Wang (Climate Dynamics, 2010)